Creating a sustainable online instructor observation system: A case study highlighting flaws when blending mentoring and evaluation - Marthann Schulte (Athabasca University Press, 2012)
Quality and accountability mandates require institutions to monitor online instruction in a uniform and complete manner. In many institutions, instructor training is sparse and faculty evaluation occurs only through end-of-course student evaluations that may or may not yield adequate information on how the instructor performs online. Consequently, the online instructor evaluation system (OIES) was developed to ensure the finest quality educational experience for online students via a systematic approach to faculty training, mentoring, and evaluation. Research has shown that combining mentoring and evaluation is not feasible, and therefore another approach is warranted.